PENGARUH KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DI KANTOR KEMENTERIAN AGAMA KABUPATEN BULUKUMBA - Nurafiah Nurafiah; ST. Syamsudduha; Ulfiani Rahman (Universitas Islam Negeri Alauddin Makassar, 2019)
This study aims to find out: 1) the description of job satisfaction in the Office of the Ministry of Religion in Bulukumba Regency, 2) the description of Organizational Citizenship Behavior at the Office of the Ministry of Religion in Bulukumba Regency, 3) the effect of job satisfaction on Organizational Citizenship Behavior at the Office Ministry of Religion of Bulukumba Regency. The type of research is an ex post facto research. Respondents in this study were 74 employees taken as a whole at the Office of the Ministry of Religion in Bulukumba Regency. Data collection techniques used were job satisfaction scale, Organizational Citizenship Behavior scale and documentation. The data analysis technique used was descriptive and inferential statistical analysis with hypothesis testing using simple linear regression analysis. The results of this study indicate that: 1) job satisfaction is good; 2) Organizational Citizen Behavior is good; 3) there is an influence of job satisfaction on Organizational Citizenship Behavior in the Office of the Ministry of Religion of Bulukumba Regency.